Internal and External Analysis for Spam Investment Perum Jasa Tirta II - Sripamesti Putri; Raden Aswin Rahadi (Green Publisher Indonesia, 2025)
Indonesia is facing increasing water demand due to rapid urbanization, industrialization, and population growth. To address this challenge, the government is prioritizing the development of Sistem Penyediaan Air Minum (SPAM) as part of its Vision Indonesia 2045*, aiming to ensure universal access to clean water while reducing groundwater dependency and environmental degradation. This study evaluates the feasibility of SPAM investment by* Perum Jasa Tirta II (PJT II), a state-owned enterprise tasked with water resource management. Using a mixed-methods approach, the study combines qualitative PESTLE analysis with quantitative financial assessments, including NPV, IRR, PBP, and PI, supported by sensitivity testing. The financial analysis reveals a positive NPV of IDR 58.3 billion, an IRR of 16.8% (exceeding the 12% WACC), a payback period of 6.2 years, and a profitability index of 1.42, confirming strong financial viability. The findings reveal that strong political backing, economic recovery, rising public health awareness, and PJT II's operational mandate support the strategic relevance of SPAM. Despite challenges such as aging infrastructure, the investment is found to be both financially and strategically viable. This study offers practical insights for aligning public infrastructure investment with national development goals and sustainable resource management.